Therapeutic Management of Paracetamol Toxicity in Dogs: A Study of Six Cases - Shah, Aditya I; Parmar, Jignesh J; Rao, Neha; Sadhu, Dashrath B; Hadiya , Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The analgesics and antipyretics such as paracetamol, bruphen and aspirin are mostly used medication in human being, paracetamol shows less side effects like less gastric irritation and bleeding (Khan, 1995). Due to its easy avaibility and non-narcotic nature people keep them in houses and consume without any advice of experts, whenever needed, and also use for their pets. Sometimes the pets specially dogs and cats also ingest accidently these medications. The reports of paracetamol toxicity especially in dogs are meager. This paper presents toxicity of paracetamol in dogs and its successful therapeutic management.